2017
DOI: 10.1038/nrm.2017.107
|View full text |Cite|
|
Sign up to set email alerts
|

Sphingolipids and their metabolism in physiology and disease

Abstract: Studies of bioactive lipids in general and sphingolipids in particular have intensified over the past several years, revealing an unprecedented and unanticipated complexity of the lipidome and its many functions, which rivals, if not exceeds, that of the genome or proteome. These results highlight critical roles for bioactive sphingolipids in most, if not all, major cell biological responses, including all major cell signalling pathways, and they link sphingolipid metabolism to key human diseases. Nevertheless… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
1,396
1
24

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 1,406 publications
(1,532 citation statements)
references
References 181 publications
(213 reference statements)
14
1,396
1
24
Order By: Relevance
“…Sphingolipid signaling has been observed to play important roles in turning on cellular pathways (Olson et al, 2015; Hannun and Obeid, 2018). However, it has only recently been possible to achieve the sensitivity of mass spectrometry to measure the levels of early sphingolipid intermediates.…”
Section: Resultsmentioning
confidence: 99%
“…Sphingolipid signaling has been observed to play important roles in turning on cellular pathways (Olson et al, 2015; Hannun and Obeid, 2018). However, it has only recently been possible to achieve the sensitivity of mass spectrometry to measure the levels of early sphingolipid intermediates.…”
Section: Resultsmentioning
confidence: 99%
“…Ceramides, members of the second largest class of membrane lipids, represent a family of more than 200 structurally related sphingolipids, compounds formed by a sphingoid base and a fatty acid linked via the amide bond (Hannun & Obeid, 2011, 2017). Over the past decades numerous studies have demonstrated that depending on their molecular structure, ceramides confer unique biophysical properties to the biological membranes (Castro, Prieto, & Silva, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Over the last 3 decades ceramides were established as second messengers regulating key cellular processes including cytoskeleton dynamics, endocytosis, protein transport and subcellular localization, cell cycle, autophagy, and apoptosis (Castro et al, 2014; Coant, Sakamoto, Mao, & Hannun, 2017; Dany & Ogretmen, 2015; Mullen, Hannun, & Obeid, 2012). Therefore, ceramides are indispensable for cellular homeostasis and control of fundamental functions, such as proliferation, migration, differentiation, adaptation to stress, survival, and senescence (Hannun & Obeid, 2008, 2017). …”
Section: Introductionmentioning
confidence: 99%
“…1 Cer is known to be a key modulator of cancer cell growth and apoptosis; conversely, S1P acts as an anti-apoptotic tumor protective agent. 2, 3 Therefore, the levels and balance of natural Cer-Sph-S1P must be well controlled.…”
Section: Introductionmentioning
confidence: 99%